2018
DOI: 10.1111/bcp.13554
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of trials comparing cefazolin to antistaphylococcal penicillins in the treatment of methicillin‐sensitive Staphylococcus aureus bacteraemia

Abstract: Our meta-analysis of retrospective data demonstrate that cefazolin is more effective and safer ASP in patients with MSSA bacteraemia from various causes. Low quality of trials, borderline high heterogeneity, and possible publication bias may limit the validity of our findings. Randomized trials are needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Two recent meta-analyses (both published after completion of our work) have compared the use of cefazolin and ASPs for the treatment of MSSA bacteremia [ 29 , 30 ]. The conclusions of these two meta-analyses were similar and consistent: the survival rates and safety profiles of cefazolin were superior to ASPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent meta-analyses (both published after completion of our work) have compared the use of cefazolin and ASPs for the treatment of MSSA bacteremia [ 29 , 30 ]. The conclusions of these two meta-analyses were similar and consistent: the survival rates and safety profiles of cefazolin were superior to ASPs.…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis conducted by Bidell et al concluded that cefazolin was associated with a significant reduction in all-cause 90-day mortality (OR, 0.63; 95% CI, 0.41 to 0.99; I 2 = 58%) and discontinuation due to AEs (OR, 0.25; 95% CI, 0.11 to 0.56; I 2 = 13%), when compared to ASPs [ 29 ]. Another meta-analysis conducted by Rindone et al demonstrated that the mortality (RR, 0.78; 95% CI, 0.69–0.88; I 2 = 51%) and withdrawals from AEs (RR, 0.27; 95% CI, 0.16 to 0.47; I 2 = 37%) were significantly lower in the cefazolin group than in the ASPs group [ 30 ]. These two meta-analyses had some differences compared with ours: (i) these two previous meta-analyses did not report the differences in AEs rates.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of endpoints were used among these observational studies, making it difficult to truly evaluate their results in a uniform fashion. A recent meta-analysis of ten studies comparing cefazolin to antistaphylococcal penicillins for MSSA BSI revealed a lower mortality rate with cefazolin and a higher rate of clinical cure [14]. Antistaphylococcal penicillins were also more likely to be discontinued due to an adverse event.…”
Section: Discussionmentioning
confidence: 99%
“…This article is based on previously conducted studies and does not contain any studies with human participants or animals performed by any of the authors. Our hypothesis was that, compared with ASPs, cefazolin would be associated with reduced mortality and have superior safety outcomes [7].…”
Section: Methodsmentioning
confidence: 99%